Expression of AQP1, AQP3, AQP4 and AQP5 in upper respiratory tract of buffaloes during different seasons. Issue 11 (2nd November 2022) - Debbarma, Sushanta; Ludri, Ashutosh; Saini, Sudha; Devi, Pooja; Kumar, Gaurav
ABSTRACT: Aquaporins (AQPs) are channels that mediate the movement of fluid and solute across the cell membrane. During hot season, evaporation through respiratory mucosa is an important mechanism for heat dissipation in buffaloes. AQP-mediated fluid movement in upper respiratory tract of buffaloes is yet to be studied. In the present study, the gene expression of AQP1, AQP3, AQP4 and AQP5 in upper respiratory tract of buffaloes were investigated during summer, spring and winter seasons. During summer, there was higher gene expression of AQP1 in nasal turbinate than winter. AQP1 was mainly localized in endothelial cells of blood capillaries of nasal turbinate. In nasal turbinate, the relative expression of AQP3 was upregulated nonsignificantly during summer and downregulated significantly during winter. The immunolocalization of AQP3 were observed in epithelial layers of nasal turbinate. The relative expression of AQP4 and AQP5 was upregulated during winter and downregulated during summer. During summer, the expression of AQP1, AQP3, AQP4 and AQP5 were downregulated in tracheal mucosa, which indicated their minor role in evaporative water loss in buffaloes. There is a seasonal variation of different AQPs in upper respiratory tract of buffaloes.